Exploring the Compositional Space of High-Entropy Alloys for Cost-Effective High-Temperature Applications - Orhan, Okan K.; Isiet, Mewael; Caparini, Lucas; Ponga, Mauricio (Frontiers in Materials, 2022)
High-entropy alloys (HEAs) are nearly equimolar multi-principal elements alloys, exhibiting exceptional thermal and mechanical properties at extreme conditions such as high- temperatures and stresses. Since the first discovery and early conceptualization of conventional HEAs nearly two decades ago, HEAs with far-from-equimolar compositions have attracted substantial interest to provide a broader range of materials properties and to adjust price fluctuations and availability of commodities. Here, we present a first-principles investigation of non-equimolar chromium-manganese-iron-cobalt-nickel (Cr-Mn-Fe-Co-Ni) HEAs and effects of molybdenum (Mo) and niobium (Nb) substitutions on cost, phase stability and solubility, mechanical and thermal performance up to 1000 K operational temperature. Virtual-crystal approximation is used to expediently approximate random solid solutions at the disordered mean-field limit. Using multi-objective metaheuristics built on a first-principles database, golden compositions are predicted for thermally well-insulated components and effective heat sinks. Replacing Co with Fe leads to substantially lower commodity costs without hindering phase stability and solubility. Lower Ni concentration leads to lower thermal conductivity, indicating better thermal insulation, while reducing Mn concentration substantially increases the thermal conductivity, indicating better performing heat sinks. Moving away from equimolar ratios commonly increases the thermal expansion coefficient which could generate larger thermal stresses. Nb and Mo substitution always lead to substantially higher commodity cost and density but with an increment in the mechanical performance due to solid-solution hardening. However, alloying with Mo and Nb is the only compositional space that reduces the thermal conductivity and thermal expansion coefficient.